Hybrid Perovskite‐Organic Flexible Tandem Solar Cell Enabling Highly Efficient Electrocatalysis Overall Water Splitting. Issue 18 (23rd March 2020) - Li, Zhen; Wu, Shengfan; Zhang, Jie; Lee, Ka Chun; Lei, Hang; Lin, Francis; Wang, Zilong; Zhu, Zonglong; Jen, Alex K. Y.
Abstract: Perovskite‐organic tandem solar cells are attracting more attention due to their potential for highly efficient and flexible photovoltaic device. In this work, efficient perovskite‐organic monolithic tandem solar cells integrating the wide bandgap perovskite (1.74 eV) and low bandgap organic active PBDB‐T:SN6IC‐4F (1.30 eV) layer, which serve as the top and bottom subcell, respectively, are developed. The resulting perovskite‐organic tandem solar cells with passivated wide‐bandgap perovskite show a remarkable power conversion efficiency (PCE) of 15.13%, with an open‐circuit voltage ( V oc ) of 1.85 V, a short‐circuit photocurrent ( J sc ) of 11.52 mA cm −2, and a fill factor (FF) of 70.98%. Thanks to the advantages of low temperature fabrication processes and the flexibility properties of the device, a flexible tandem solar cell which obtain a PCE of 13.61%, with V oc of 1.80 V, J sc of 11.07 mA cm −2, and FF of 68.31% is fabricated. Moreover, to demonstrate the achieved high V oc in the tandem solar cells for potential applications, a photovoltaic (PV)‐driven electrolysis system combing the tandem solar cell and water splitting electrocatalysis is assembled. The integrated device demonstrates a solar‐to‐hydrogen efficiency of 12.30% and 11.21% for rigid, and flexible perovskite‐organic tandem solar cell based PV‐driven electrolysis systems, respectively. Abstract : Phenmethylammonium bromide (PMABr) applied as passivation agent for wide‐bandgap perovskite solar cells significantly improves the photovoltaic performance in 2‐terminal (2T) perovskite‐organic tandem solar cells. The novel structure of 2T perovskite‐organic tandem solar cells provide a promising strategy to explore the advanced application in photovoltaic‐driven water splitting system and also demonstrates the advantages of perovskite‐organic configuration on flexible tandem solar cells.